The Community Service Program for Beginners to Improve the English Language Skills of Karang Taruna Youth through a Short Course in Dukuh Jetak Sindangwangi Brebes Central Java - Dede Nurdiawati; Syauqi, Achmad; Rejeki Pramudyawardhani, Sri; Fatmawati, Dewi; Salsabilla, Assifa (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
A Community Service Program using the Service-Learning method was implemented in Dukuh Jetak Village, Sindangwangi, Brebes, Central Java, aimed at improving the English language skills of Karang Taruna youth through a short course. This method combines academic learning with community service, allowing participants to learn through direct experience. The preparation stage included initial coordination, field observations, needs analysis, and the development of English modules. The implementation consisted of interactive workshops integrating English and information technology, as well as weekly courses over twelve weeks. Initial evaluations indicated that participants still faced difficulties in understanding English texts and expressions, with an average pre-test score of 33.81%. The program showed positive impacts on improving English skills and learning motivation among the village youth. However, challenges such as low learning interest require innovative approaches. The program aims to empower youth through education, opening greater opportunities for a brighter and more productive future